de Haas-van Alphen effect of correlated Dirac states in kagome metal Fe3Sn2 - Ye, Linda; Chan, Mun K.; McDonald, Ross D.; Graf, David; Kang, Mingu; Liu, Junwei; Suzuki, Takehito; Comin, Riccardo; Fu, Liang; Checkelsky, Joseph G. (Nature communications, 2019)
Primarily considered a medium of geometric frustration, there has been a growing recognition of the kagome network as a harbor of lattice-borne topological electronic phases. In this study we report the observation of magnetoquantum de Haas-van Alphen oscillations of the ferromagnetic kagome lattice metal Fe 3 Sn 2 . We observe a pair of quasi-two-dimensional Fermi surfaces arising from bulk massive Dirac states and show that these band areas and effective masses are systematically modulated by the rotation of the ferromagnetic moment. Combined with measurements of Berry curvature induced Hall conductivity, our observations suggest that the ferromagnetic Dirac fermions in Fe 3 Sn 2 are subject to intrinsic spin-orbit coupling in the d electron sector which is likely of Kane-Mele type. Our results provide insights for spintronic manipulation of magnetic topological electronic states and pathways to realizing further highly correlated topological materials from the lattice perspective. The kagome lattice is increasingly known as a host for correlated topological electronic states. Here, Ye et al. report quantum de Haas-van Alphen oscillations of a ferromagnetic kagome material Fe3Sn2, where bulk electronic Dirac fermions are found to be modulated by rotation of the magnetic moment.